Mediation of Agency Cost on Governance in Company Financial Performance - Ashari Sofyaun; Asrid Juniar; Rini Rahmawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Financial performance in the perspective of governance with agency cost is the research objective. The study was conducted during the period 2013-2021 on state-owned companies on the Indonesian stock exchange with a purposive sampling method approach. Managerial ownership, leverage and board size as representatives of corporate governance. In measuring financial performance indicators of ROA and firm value are used. SEM-PLS multivariate analysis was used as a data analysis technique. affected by leverage, agency costs and return on assets is significantly Leverage and agency costs have a significant effect on return on assets. leverage and board size have a significant effect on agency costs. Leverage and board size were successfully mediated by agency costs in influencing firm value and ROA.